Analysis of The Larger and Smaller Units of Translation in Feature News - Adiyatma Rahmadanto; Doris Yolanda Saragih (CV. Tirta Pustaka Press, 2025)
Communication is an important aspect to allow human to interact with one another. It is quite simple and complex function in daily life. Mass media such as news is one of the types of communication that human use to receive information. Feature news stands out among other news due to its narrative and emotional aspects. With news being one of the roles to spread information to a diverse audience with different background such as language, it creates barriers to the non-English speaker audience. This study aims to explore translation roles with strategies and procedures to overcome communication barriers. It examines the process of translation by looking to the larger and smaller units of translation and how those units affect the Target Text naturalness by comparing the Source Text and Target Text using theories by Peter Newmark, Eugene Nida, Jean-Paul Vinay, and Jean Darbelnet as analytical frameworks.